Programmed Death Ligand 2 Gene Polymorphisms Are Associated With Lung Adenocarcinoma Risk in Female Never-Smokers - Liang, Sheng-Kai; Chien, Li-Hsin; Chang, Gee-Chen; Tsai, Ying-Huang; Su, Wu-Chou; Chen, Yuh-Min; Huang, Ming-Shyan; Lin, Hsien-Chih; Fang, Wen-Tsen; Hung, Hsiao-Han; Jiang, Shih-Sheng; Chen, Chih-Yi; et al. (Frontiers in Oncology, 2021)
Objectives: Lung cancer in never-smokers is a distinct disease associated with a different genomic landscape, pathogenesis, risk factors, and immune checkpoint inhibitor responses compared to those observed in smokers. This study aimed to identify novel single nucleotide polymorphisms (SNPs) of programmed death-1 (encoded by PDCD1) and its ligands, programmed death ligand 1 (CD274) and 2 (PDCD1LG2), associated with lung cancer risk in never-smoking women. Materials and Methods: During September 2002 and July 2012, we enrolled never-smoking female patients with lung adenocarcinoma (LUAD) (n=1153) and healthy women (n=1022) from six tertiary hospitals in Taiwan. SNP data were obtained and analyzed from the genome-wide association study dataset and through an imputation method. The expression quantitative trait loci (eQTL) analysis was performed in both tumor and non-tumor tissues for the correlation between genetic expression and identified SNPs. Results: A total of 12 PDCD1LG2 SNPs related to LUAD risk were identified in never-smoking women, including rs2381282, rs4742103, rs4237162, rs4742104, rs12237624, rs78096119, rs6476988, rs7857315, rs10975178, rs7854413, rs56001683, and rs7858319. Among them, six tagged PDCD1LG2 SNPs rs2381282, rs4742103, rs4237162, rs4742104, rs78096119, and rs56001683 were significantly associated with LUAD risk. Specifically, two PDCD1LG2 SNPs, rs12237624 and rs78096119, were associated with previous pulmonary tuberculosis infection in relation to LUAD susceptibility. Through an eQTL assay, we found that rs2381282 (p < 0.001), rs12237624 (p = 0.019), and rs78096119 (p = 0.019) were associated with the expression levels of programed death ligand 2. Conclusions: Novel SNPs of programed death ligand 2 associated with lung adenocarcinoma risk were identified. Among them, two SNPs were associated with pulmonary tuberculosis infection in relation to lung adenocarcinoma susceptibility. These SNPs may help to stratify high-risk populations of never-smokers during lung cancer screening.